Рецензія на книгу Delacourt S. Shopping for Votes: How Politicians Choose Us and We Choose Them - Лупул, Тарас (Історико-політичні проблеми сучасного світу, 2020)
Рецензія на книгу Delacourt S. Shopping for Votes: How Politicians Choose Us and We Choose Them